Pendampingan Pembelajaran Siswa Kelas I SD Negeri Lialang Di Masa Pandemi Covid-19 - Ayu Saskia Norma Wardani; Ita Rustiati Ridwan (Jurnal Pengabdian Masyarakat PGSD, 2022)
Advances in digital technology growth have become a learning solution when the Covid-19 pandemic has had a lot of positive effects in the world of education. Technology becomes a tool for some learning problems. One of them is what happened to students of State Elementary School of Lialang. The problem with the first-grade students of State Elementary School of Lialang was that there were students who find it difficult to learn and have difficulty understanding the material. The author's purpose in assisting students is to help students who do not understand the material given by the teacher. The excellent community service work program that the author does in the field of education is a mentoring program for first-grade students’ learning during the Covid-19 pandemic. The activity was carried out for 1 month in July 2021 in Lialang Village, precisely at State Elementary School of Lialang, Serang City, Banten online and offline. The online learning process used Whatsapp Group Video Calls, while offline learning through visit once a week 5 to 6 students go to school for 2 hours by complying with the Covid-19 health protocols. The authors hope that the program that be implemented goes well and after the implementation of this program can help first-grade students who have difficulty in the learning process. In the future, the authors hope that the learning process during this pandemic will continue to make students enthusiastic about learning and can make the Indonesian people smarter even though trough different modes.